Infant outcome of 957 singletons born after frozen embryo replacement: the Danish National Cohort Study 1995-2006 - Pinborg, Anja; Loft, Anne; Aaris Henningsen, Anna-Karina; Rasmussen, Steen; Andersen, Anders Nyboe (Fertility and sterility, 2010)
To examine infant outcome of singletons born after cryopreservation of embryos (Cryo). National population-based controlled follow-up study. Denmark, 1995-2007. The study population was 957 Cryo singletons (Cryo-IVF, n=660; Cryo-ICSI, n=244; Cryo-IVF/-ICSI, n=53). The first control group was all singletons born after fresh IVF or intracytoplasmic sperm injection (ICSI) during the same period (IVF, n=6904; ICSI, n=3425). The second control group comprised a random sample of non-assisted reproductive technology (ART) singletons (n=4800). All observations were obtained from national registers. Low birth weight (LBW; <2500 g), preterm birth (PTB; <37 weeks), congenital malformations, mortality, and morbidity. Birth weight was higher in Cryo (mean=3578 g, SD=625) versus fresh (mean=3373 g, SD=648) and in Cryo versus non-ART (mean=3537 g, SD=572), and this was also the case for first birth only. Lower adjusted risk of LBW (odds ratio [OR]=0.63; 95% confidence interval [CI], 0.45-0.87) and PTB (OR=0.70; 95% CI, 0.53-0.92) was observed in Cryo versus fresh. Similar LBW and PTB rates were observed when comparing Cryo with non-ART, but the perinatal mortality rate was doubled in Cryo (1.6%) compared with non-ART (0.8%) singletons, and the adjusted risks of very preterm birth (<34 weeks) and neonatal admittance were also significantly increased. No significant differences in the prevalence rates of birth defects, neurological sequelae, malignancies, and imprinting-related diseases were observed between the Cryo and the two control groups. However higher malformation and cerebral palsy rates were observed in the total Fresh vs. non-ART group. Cryo singletons have better neonatal outcome than offspring after fresh ET but poorer compared with non-ART singletons.